The association between cultural capital and academic writing skills: a case study of level one semester one communication skills students in the faculties of arts and social sciences at midlands state university - Mugomba, Moreen (Midlands State University, 2017)
This study was carried out to investigate the association between cultural capital and academic writing skills of level one semester one Communication Skills students with particular reference to Midlands State University. This study was informed by the cultural capital framework. A case study design was used. Questionnaires were administered to 117 level one semester one Communication Skills students of which 53.6% were females. Four lecturers were interviewed while assignments were analysed as part of document analysis. The researcher found out that while some variables of cultural capital like father’s occupations, parental level of education and language are associated with academic writing skills of students, others as areas of residence and schools attended are not. The study made a number of recommendations aimed at improving and enhancing academic writing skills of students. The study recommended that parents should encourage the use of English at home and expose their children to various forms of media such as televisions.